Effectiveness of the safety campaign program in the Soekarno-Hatta Airport Flight Operational Safety Area - Nurhayu Mairani; Harits Hijrah Wicaksana (Green Publisher Indonesia, 2025)
Aviation safety is the main aspect that must be maintained in airport operations. One of the efforts made is through a safety campaign program to increase public awareness of the policy of prohibiting activities that interfere with the Aviation Operational Safety Area (KKOP) at Soekarno-Hatta Airport. This study aims to analyze the effectiveness of the safety campaign program in supporting the policy by identifying challenges and formulating recommendations for improvement. This study uses a qualitative approach with interview, observation, and document analysis methods. The analysis was carried out based on the effectiveness theory from Siagian, Steers, and Sutrisno which included aspects of successful achievement of goals, integration with stakeholders, adaptation to challenges, community satisfaction, and program productivity. The results of the study show that the safety campaign program has had a positive impact, such as increasing public awareness and supporting regulations. However, there are obstacles such as limited resources, low community participation, and less optimal coordination between stakeholders. Therefore, increased collaboration between related parties, optimization of digital technology in campaigns, and periodic evaluations are needed to ensure the effectiveness of the program in supporting flight safety at Soekarno-Hatta Airport.